Influence of ammonium hydrogen carbonate molar ratio on structural and morphological properties of Y2O3nanoparticles. Issue 1 (January 2021) - Kumar, Sushil; Tripathi, Harshit; Bhardwaj, Sumit; Sharma, J D; Batra, Uma
Abstract: The co-precipitation synthesis is considered as one of the greatest wet chemical route to produce nanoparticles because of its yield and control over synthesis parameters. In this manuscript, Yttria (Y2 O3 ) nanoparticles (YNPs) have been synthesized through direct titration precipitation process using ammonium hydrogen carbonate (AHC) as precipitant to metal ion molar ratio (M 3+ ) in acidic medium condition. The molar ratio [R= (NH4 HCO3 )/(M 3+ )] varies from 0.35 M to 0.55 M with constant metal ion (M 3+ =0.1M) concentration. The influence of R-value on crystallographic structure, particle size, surface morphology of YNPs are comprehensively studied. Rietveld refined parameters confirm the formation of pure cubic yttria phase in calcined powders. The FTIR results confirm the presence of Y-O-Y and Y-O bands. The influence of R-value on the development of morphological aspects was observed using field emission scanning electron microscopy which shows pseudo spherical morphology with a particle size range of 24.63±5.6 nm to 31.46±5.1 nm. TGA/DSC results confirm the complete transformation of intermediate yttrium compounds to pure cubic Y2 O3 single phase at a temperature of 780°C.